PENERAPAN MEDIA PEMBELAJARAN AUDIO VISUAL PADA KETERAMPILAN MENULIS PEMELAJAR BIPA - Nisa, Rahmatyana Azizatu; Muzaki, Helmi (STKIP PGRI SUMENEP, 2024)
Writing skill is the most difficult language skill to be mastered by BIPA learners. One of the efforts to reduce these difficulties is by choosing effective and interesting learning media. This research was written to describe the use of audio-visual media in learning to write BIPA learners. The research method chosen is descriptive-qualitative and uses the type of library research to find data about the use of audio-visual media. Based on the data obtained, audio-visual media is considered effective to use in writing skills because this media is not only in the form of writing or sound but also equipped with images that can provide a real picture of the material being studied by BIPA learners. Broadly speaking, the steps of applying audio-visual learning media are divided into three stages, namely preparation, implementation, and evaluation.